Verbal Barriers to Effective Intercultural Communication: A Case Study of International Students in Hungary (International Journal of Psychosocial Rehabilitation, 2020)
In the past years, the number of international students admitted to Hungarian higher education institutions increased rapidly. Students from different cultural and linguistic backgrounds encounter several challenges in the new host country. Therefore, the main purpose of the present study is to shed light on intercultural communication experiences by international students in Hungary, with particular attention to the verbal communication barriers. The participants of the study were 75 foreign students who are studying at Hungarian universities. All of them are second language (L2) speakers of English except for one student, who is an English native speaker. Data collection was conducted through survey questionnaires and interviews. The results show that verbal communication is the main barrier that participants experience while communicating with people with various cultural backgrounds. Moreover, the analysis reveals these verbal communication barriers arise for different reasons, such as speaking different mother tongues, not speaking a shared language fluently, using wrong words, and having a foreign accent.